The growth and contemporary challenges of Islamic microfinance in Bangladesh - Md Faruk, Abdullah; Biplob, Hossain (2019)
Microfinance industry is one of the a sectors of Bangladesh which has been experienced a tremendous growth in last three decades. The aim of developing microfinance schemes is to provide business opportunities for the poor in order to promote their financial health. Initially, the conventional model has only been used to give financing. With the passage of time, Islamic model of financing is also included under microfinancing programs. Nowadays, both conventional and Islamic models are currently being used to provide financing. However, several researchers believe that the Islamic model of financing is more effective as it considers basic human needs. But, the growth of Islamic microfinance is not as it is expected. At present, Islamic Microfinance Institutions (IMFIs) in Bangladesh are facing a number of challenges due to its nature, lack of resources and regulatory support. Therefore, this study is going to deliberate rationales behind the growth of Islamic microfinance industry in Bangladesh. Moreover, current challenges and possible suggestions of this industry are also discussed. The article has been mainly designed based on secondary data. It is expected that the output of this study might be beneficial for microfinance practitioners, learners and researchers especially those who have interest on this issue.